2016
DOI: 10.1126/science.aab3907
|View full text |Cite
|
Sign up to set email alerts
|

Climate confusion among U.S. teachers

Abstract: Teachers' knowledge and values can hinder climate education

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
119
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(128 citation statements)
references
References 8 publications
3
119
0
6
Order By: Relevance
“…A teacher's beliefs can directly affect how they approach teaching and learning in their classroom. In science, where some topics are controversial, teacher beliefs can affect decisions as to whether or not to teach material or influence teacher's comfort in teaching that material (Plutzer et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A teacher's beliefs can directly affect how they approach teaching and learning in their classroom. In science, where some topics are controversial, teacher beliefs can affect decisions as to whether or not to teach material or influence teacher's comfort in teaching that material (Plutzer et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These topics have not universally been included in state science standards and, due to their controversial nature, may create resistance to adopting the NGSS by teachers who do not want to make waves or who hold ideas that contradict the established science (Dawson, 2012;Plutzer, McCaffrey, Hannah, Rosenau, Berbeco, & Reid, 2016).…”
Section: Science Content In the Ngssmentioning
confidence: 99%
“…Preparing students for a world in which the effects of climate change are omnipresent requires a new model for science education-one that emphasizes the intellectual and practical abilities needed to work across disciplines to develop responses to global challenges (Melillo et al 2014;Plutzer et al 2016). The need for new models of education is exacerbated by ongoing declines in literacy in science, technology, engineering, and mathematics (STEM) in the United States (Brewer and Smith 2011;PCAST 2012).…”
Section: Climate Change: a Call For New Forms Of Science Educationmentioning
confidence: 99%
“…For example, students often come to college confused about the causes of climate change. Plutzer et al [21] reported that 31% of middle school science and high school biology teachers explicitly send contradictory messages regarding the causes of climate change: they teach students that both anthropogenic and natural causes may be responsible for the observed changes to our climate. The instructors explicitly addressed this and other misconceptions about climate change as discussed in the public sphere.…”
Section: Curriculum Design and Pedagogymentioning
confidence: 99%
“…However, both the geographic location of Stonehill (located near Boston, a city determined to be experiencing higher than average sea level rise [36] and predicted to experience above average temperature increases [37] in the coming decades) and the timing of the course (one year after President Obama was re-elected, noting "the destructive power of a warming planet" in his victory speech) provided excellent opportunities to teach about climate change and its solutions to a broad student population in the general education program. Furthermore, the ENV faculty were eager to respond to both anecdotal evidence (later documented in [21]) that students' prior exposure to climate change education may have been misinformed or incomplete and to the evidence that even well-educated people often failed to alter their attitudes and behaviors to become part of the solution [38][39][40][41][42]. As such, in this study we aim to answer two primary research questions: (1) whether and to what extent The Ethics and Science of Climate Change contributed to shifts in student views on climate change; and (2) whether and to what extent such shifts were retained two years later.…”
Section: Introductionmentioning
confidence: 99%